Analisis Pembinaan Prestasi terhadap Manajemen Olahraga Sekolah Sepak Bola (SSB) Se-Kabupaten Pati Tahun 2019 - Muhammad Syahroni; Galih Dwi Pradipta; Buyung Kusumawardhana (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2020)
The results of the study show that organizing is still lacking because the trainer also doubles as an administrator, the coach should focus on fostering the athletes while stewardship is managed by someone else, from good facilities and infrastructure the training can run well, so the training methods provided by the trainer will go smoothly. Funding at SSB is still lacking, because it only relies on monthly fees, the trainers who train SSB have no training license but rather train from the experience gained as a player or as a Sports Coaching student. The training program of the seven SSBs is good, from the scheduled training program, the training program is communicated so that the implementation process can run well. The achievements are quite good, from the junior level championship can train mentally and spotivity.Conclusions in fostering achievement towards sports management Soccer schools (SSB) throughout Pati Regency are still not good enough. Suggestions in this study Soccer schools should have good organization and management, so that the planned program can run well and coordinated, the coaching process must be followed up and improved, because with coaching that is gradual and continuous, it will indirectly benefit the parties SSB itself, more and more native sons will become professional players.